Frequency of Cyanotic Heart Disease in Infants of Diabetic Mothers - Muhammad Idrees, Nayab Syed, Abid Imran, Waqas Iqbal, Romana Bibi, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of cyanotic heart disease in infants born to diabetic mothers referred to Tertiary Care Hospital. Materials: This Cross-Sectional Study was conducted in the Pediatrics Department of Hayatabad Medical Complex, Peshawar from July 2021 to July 2022. In this study, a total of 262 patients were to determine the frequency of cyanotic heart disease in infants born to diabetic mothers referred to the Pediatrics Department of Hayatabad Medical Complex, Peshawar. The sampling technique was non-probability consecutive sampling. Results: The age of the participants among 262 patients was analyzed as n= 1-15 Days was 170(64.9%) 16-28 Days was 92(35.1%). The mean age was 9±1.87 days. The distribution of gender among 262 patients was analyzed as n= Male was 142(54.2%) and Female was 120(45.8%).The distribution of weight among 262 patients was analyzed as n= less than or Equal to 4.5 kg was 126(48.1%) and More than 4.5 kg was 136(51.9%). Mean weight 5.1±1.87kg. Distribution of Duration of diabetes in mothers (years) among 262 patients was analyzed as n= 1-5 Years was 135(51.5%) and More than 6 Years was 127(48.5%). Mean duration was7.1±1.12 years. The distribution of Cyanotic Heart Disease among 262 patients was analyzed as n= Yes was 48(18.3%) and No was 214(81.7%). Practical implication: To determine the frequency of cyanotic heart diseases in children born of a diabetic mother, its prompt diagnosis and management to reduce neonatal morbidity and mortality. Conclusion: In this high-risk population useful assessment and early CHD diagnosis are strongly suggested, and echocardiography is advised as soon as feasible for all newborns of diabetes mothers. Prenatal CHD screening program for neonates of diabetes moms are required in our setup. Therefore, additional confirmation is anticipated in a study of a larger diabetic population. Keywords: Gestational diabetes mellitus, Congenital heart diseases, pre-gestational diabetes mellitus, Diabetic mothers